ANALISIS HASIL PERANCANGAN PEMBANGKIT LISTRIK TENAGA SEPEDA STATIS DI FITNESS CENTER TERMINAL TRANSIT BAHAN BAKAR MINYAK PERTAMINA WAYAME AMBON - Andri Ashfahani; Riezqi Fajar; Mauluddin Eko Setiawan; Endang Suhendar; Wildan Hariz Sinatrya (Jurnal Teknologi Elektro, 2017)
Nowadays, energy efficiency is an issue that is being faced by the industry. By increasing energy efficiency, production costs can be reduced to its lowest level. Terminal Transit Bahan Bakar Minyak Pertamina Wayame, Ambon as a part of the government committed to get actively involved in the implementation of the energy efficiency program. The innovation is done by converting the mechanical energy of the stationary bike to electrical energy by the generator mounted on the bike. Workers who do exercise by nature are wasting some energy. This energy of a worker is converted to mechanical energy by the stationary bike. Mechanical energy of the stationary bike is converted to electrical energy by DC generator mounted on the bike, which is the ultimate output. Finally, the electrical energy generated by stationary bike will then be stored in the battery. The energy stored in the battery is ready to be used as an energy source for LED lights scattered on the building. The results show that the stationary bike generator can generate 0.12 kW of power and save Rp. 468,594.30 per year.